L'inclusion scolaire des élèves en situation de handicap au Burundi : ressources et obstacles du point de vue des acteurs du système éducatif - Josias Ndikumasabo; Agathe Evin; Jacques Saury (Nantes Université, 2018)
The purpose of this exploratory and comprehensive study is to assess the barriers and opportunities to the implementation of the policy of school inclusion of the children with disabilities in Burundi from the point of view from different actors involved directly in this policy. It was conducted in reference to the Grounded Theory (Strauss & Corbin, 1990). The results reveal four major barriers: (a) limits of the possibilities of educational system of Burundi to welcome all children; (b) incompatibility of the educational practices in front of pupils with disabilities;(c) limits of the burundian government policy to implement the right of education; (d) representations and stigmatizing faiths against children with disabilities. However, the results also highlight two already available resources: (a) educational initiatives favoring the inclusion, and (b) vectors in favour of the implementation of an inclusive pedagogy. Furthermore, the results show conditions associated to the success of an inclusive education especially human resources and school environment which are required to implement an inclusive education.